2022
DOI: 10.1111/exd.14664
|View full text |Cite
|
Sign up to set email alerts
|

Ultra‐high frequency ultrasound detection of the dermo‐epidermal junction: Its potential role in dermatology

Abstract: Traditional high‐frequency ultrasound (HFUS; 20 MHz) is a non‐invasive method used to study skin in vivo but is not able to measure skin thickness accurately and to identify the dermal‐epidermal junction (DEJ). Ultra‐high frequency ultrasound (UHFUS; 70–100 MHz) has sub‐millimetre resolution comparable to histology. The aim of this study was to identify, by UHFUS, the DEJ and to describe skin differences in healthy individuals by providing a measure of skin thickness, based on age and gender. We also described… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Recently, Granieri et al for the first time identified the dermo‐epidermal junction with UHFUS (70 MHz) 37 . This finding can be useful to improve ultrasonographic pre‐surgical assessment of melanoma in the future.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Recently, Granieri et al for the first time identified the dermo‐epidermal junction with UHFUS (70 MHz) 37 . This finding can be useful to improve ultrasonographic pre‐surgical assessment of melanoma in the future.…”
Section: Discussionmentioning
confidence: 93%
“…Moreover, in case of diagnostic incisional biopsy (eg, large lentigo maligna/ lentigo maligna melanoma on the face), UHFUS can guide the clinicians indicating the point of maximum depth. 37 This finding can be useful to improve ultrasonographic pre-surgical assessment of melanoma in the future.…”
Section: Oranges Et Al-ultrasound In Melanoma Managementmentioning
confidence: 83%
“…The fingernail examination was performed in a seated position with hands placed on a table. The proper distance of the probe from the skin, to permit imaging of superficial structures, was maintained with an appropriate amount of gel [ 23 ]. The fingernail apparatus was assessed in B-MODE with a longitudinal section on the middle point of the lamina.…”
Section: Methodsmentioning
confidence: 99%
“…The patients were naive to previous conventional and biologic systemic therapies and were evaluated at baseline and after 1 month and after 3 months from the beginning of biologic therapy. At each visit, the clinical investigation was performed by a dermatologist expert in psoriasis who collected a photographic record of the patient and assessed clinical disease parameters such as the psoriasis area severity index (PASI), NAPSI, modified (m)-NAPSI calculated on Diagnostics 2023, 13, 2716 3 of 11 the nail with major clinical alterations and dermatology life quality index (DLQI) [21][22][23]. For the US examination of the nail apparatus, a UHFUS with a 70 MHz probe was used (Vevo MD ®® FUJIFILM VisualSonics, Toronto, ON, Canada).…”
Section: Methodsmentioning
confidence: 99%
“…UHFUS provides clinicians and researchers with a powerful tool to delve deep into the skin's microanatomy, revealing intricate details that were previously inaccessible without invasive procedures. The technique captures comprehensive images of various skin components, such as the dermo-epidermal junction, hair follicles, pilo-erector muscles, and blood vessels [15][16][17][18][19][20][21]. The distinct patterns observed through UHFUS imaging could assist in the early detection of PG, enabling timely intervention and management.…”
Section: Introductionmentioning
confidence: 99%